miR-4666-3p and miR-329 Synergistically Suppress the Stemness of Colorectal Cancer Cells via Targeting TGF-β/Smad Pathway - Ye, Jun; Lei, Jiacai; Fang, Qingqing; Shen, Yimin; Xia, Wenjie; Hu, Xiaoge; Xu, Qiuran; Yuan, Hongjun; Huang, Jian; Ni, Chao (Frontiers in Oncology, 2019)
Quiescent caner stem cells are identified as a subpopulation of colon cancer cells in dormant state and possess strong stem-cell like characteristics. Previously, we have identified this subpopulation in colorectal cancer (quiescent colon cancer stem cells, QCCSCs), and find QCCSCs are sensitive to the apoptotic effect of IFN-γ, which is attributed to their high IFN-γR expression levels. Microarray and bioinformatic analysis indicate miR-4666-3p is low expressed in QCCSCs and target IFN-γR1/2, which is proved by luciferase assay and western-blot. Furthermore, we find miR-4666-3p could also target TGF-βR1 to block the activation of TGF-β1/Smad pathway, therefore function as a tumor suppressor gene to inhibit the stemness of colon cancer cells. Besides, compared with QCCSCs, we find the TGF-β1 expression also decreased with the weakening of stemness properties. In terms of mechanism, our result reveal TGF-β1 is the target gene of miR-329, which is also high expressed in non-QCCSCs. Thereafter, we perform gain- and loss- function experiments to confirm the synergistic effect between miR-4666-3p and miR-329 in blocking the activation of TGF-β/Smad pathway. Finally, we evaluate the expression of both miR-4666-3p and miR-329 in 73 tumor specimens and paired normal tissue, and find both two miRNAs are related to unfavorable prognosis and advanced tumor stage in colorectal cancer. Our study revealed a novel epigenetic regulation mechanism in colon cancer stem cells, which could be exploited as a novel therapeutic strategy for cancer treatment.